Persistent Organic Pollutants in Human Milk from Central Italy: Levels and Time Trends. (17th July 2011) - Guerranti, Cristiana; Palmieri, Michela; Mariottini, Michela; Focardi, Silvano Ettore
Abstract : Persistent organic pollutants (POPs) such as HCB, p, p ′ -DDE, and PCBs were measured in Italian breast milk. This work is part of a study on human milk, adipose tissues, and food carried out in the same area over the last 20 years. The results showed the prevalence of p, p ′ -DDE and PCBs over HCB. Comparison of our results with those of previous studies carried out in the same area showed that concentrations are decreasing. No statistically significant differences in organochlorine levels were found when the samples were divided into maternal age classes and into the categories "primiparae" and "multiparae". In order to quantify the amount of the molecules of interest transmitted by mother to child during breast feeding, we estimated the daily intake of each class of compounds: our results indicated that HCB and p, p ′ -DDE were several times lower than the safety thresholds.